2015
DOI: 10.3390/ijms160612076
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Mesenchymal Progenitor Cells Engraft into Rabbit Articular Cartilage

Abstract: Mesenchymal stem cells (MSCs) are known to have the potential for articular cartilage regeneration, and are suggested for the treatment of osteoarthritis (OA). Here, we investigated whether intra-articular injection of xenogeneic human adipose-derived mesenchymal progenitor cells (haMPCs) promoted articular cartilage repair in rabbit OA model and engrafted into rabbit articular cartilage. The haMPCs were cultured in vitro, and phenotypes and differentiation characteristics of cells were evaluated. OA was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 47 publications
4
51
0
1
Order By: Relevance
“…haMSC isolation was described previously [2]. haMSC (1 × 10 6 ; passage 3) were incubated with 10 μM DiD fluorescent dye (Life Technologies & Molecular Probes, USA) for 50 min at 37 °C according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…haMSC isolation was described previously [2]. haMSC (1 × 10 6 ; passage 3) were incubated with 10 μM DiD fluorescent dye (Life Technologies & Molecular Probes, USA) for 50 min at 37 °C according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation of DiD-haMSCs was performed as previously reported [2]. Briefly, for adipogenic and osteogenic differentiation, cells were seeded and grown in StemPro® adipogenesis differentiation medium and StemPro® osteogenesis differentiation medium (Gibco, USA) for 3 weeks, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The improvement had been observed macroscopically where cartilage lesion had been covered by repaired tissue and the surface was relatively smooth. The histological assessment revealed only a few fissures, few cracks, and an almost continuous superficial zone [85]. Another study showed that injected AMSC migrated to the synovial membrane and meniscus, however not in cartilage.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…(24,25) However, many of the cells used in these studies were pretreated with chondrogenic/osteogenic factors, and whether these nonskeletal cells produce functional bone and associated tissues, or whether they induce local cells to undergo a repair process in vivo, (26,27) is not known. (24,25) However, many of the cells used in these studies were pretreated with chondrogenic/osteogenic factors, and whether these nonskeletal cells produce functional bone and associated tissues, or whether they induce local cells to undergo a repair process in vivo, (26,27) is not known.…”
Section: Pluripotent Stem Cells (Embryonic Stem Cells) and Induced Plmentioning
confidence: 99%